Gender linguistics: social, psychological characteristics (Eurasian Journal of Philology Science and Education, 2016)
This article focuses on gender linguistics that studies the language features between men and women.In this scientific paper, there is given social linguistic study public, sociological, political, cultural, regional, areal problem of the nature of language, as well as family, youth, work, urban, leadership, and the language of the elite criminals and thieves, attention is drawn to the fact that gender linguistics is closely related to sociolinguistics.The article provides information about: the role of linguistic features between men and women in the culture of the people and ethnic group, the cultural and national values in the language of men and women who have kept in different structural texts of the norm of gender stylistic etiquette about the difference between men and linguistic characteristics Furthermore the influence of gender on the acquisition of language features and addressing gender opposition in the formation of linguistic world.
Keywords: gender linguistics; psycholinguistics; sociolinguistics; cultural linguistics.